PROBLEMS OF QUALIFICATION AND EMPLOYMENT LAW PROTECTION OF CROWDWORKERS - Dragićević, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Even though increased success of digital platform work has been recorded only recently, numerous problems which refer to employment law protection and social protection of crowdworkers (due to problems of classifying specific individuals as employees) are not novelty. For many years, “atypical” workers and crowdworkers have faced problems while attempting to obtain labor and social protection. Despite numerous differences, majority of countries have made employment law protection available to those platform workers who meet the requirements of legal definition of “employee” (or “worker”, as explicitly defined by specific legislations). In other words, legal definition of employee or dependent contractor represents the entrance to the area of employment law protection. However, both national and international legislators have demonstrated a certain degree of inertness in terms of avoiding to adjust the legal concept of “employee” (or subordinate, as some legislations have defined it) to new social and conomic context. Consequently, in terms of traditional concept of “employee”, crowdworkers cannot be qualified as a subordinate, which puts digital platform workers beyond the scope of labor, social and tax legislations. On the other hand, when it comes to traditional legal categories, classifying crowdworkers as independent contractors does not diminish their need for adequate protection, primarily in terms of fair financial compensation for work, clearly limited working hours, health and safety at work, protection in case of illness, injury at work, maternity leave or freedom of association. Therefore, national legislators should revise justifiability and proportionality of legislation which is applied to economic cooperation, and consider specificities of economic cooperation business models and tools that can be used for solving issues of defining employment law protection of crowdworkers and identifying entity(ies) with legal status of employer.